2012
DOI: 10.1128/jb.00961-12
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs Binding to the Nucleoid Protein HU in Escherichia coli

Abstract: Some unidentified RNA molecules, together with the nucleoid protein HU, were suggested to be involved in the nucleoid structure of Escherichia coli. HU is a conserved protein known for its role in binding to DNA and maintaining negative supercoils in the latter. HU also binds to a few RNAs, but the full spectrum of its binding targets in the cell is not known. To understand any interaction of HU with RNA in the nucleoid structure, we immunoprecipitated potential HU-RNA complexes from cells and examined bound R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…We envision that these proteins and DNA gain access to the extracellular milieu by passive or active cell lysis or autolysis (Claverys and Havarstein, 2007;Rice and Bayles, 2008). It is intriguing that HU is indispensable for the signal recognition particle (SRP) complex in Grampositive bacteria (Nakamura et al, 1999); recently, it was shown that HU may even associate with the 4.5s RNA of the SRP of E. coli (Macvanin et al, 2012). It is possible that HU could exit the bacterial cell via this system.…”
Section: Discussionmentioning
confidence: 99%
“…We envision that these proteins and DNA gain access to the extracellular milieu by passive or active cell lysis or autolysis (Claverys and Havarstein, 2007;Rice and Bayles, 2008). It is intriguing that HU is indispensable for the signal recognition particle (SRP) complex in Grampositive bacteria (Nakamura et al, 1999); recently, it was shown that HU may even associate with the 4.5s RNA of the SRP of E. coli (Macvanin et al, 2012). It is possible that HU could exit the bacterial cell via this system.…”
Section: Discussionmentioning
confidence: 99%
“…25 Pettijohn and Hecht in 1974 first suggested that RNA plays a role in maintaining the nucleoid structure in E. coli. 26 Recently, Macvanin et al 27 reported that 2 novel non-coding RNAs bind to the architectural DNA-binding protein HU and affect the nucleoid structure, implying that RNA molecules play an important role in genome organization. Moreover, we expect that some of the asRNAs and intraRNAs may code for small peptides, further increasing the protein-coding potential of genomes.…”
Section: Discussionmentioning
confidence: 99%
“…77,78 More recently, they have also been demonstrated to be involved in nucleoid morphology and chromosome formation and maintenance. 79 …”
Section: Discussionmentioning
confidence: 99%